2022
DOI: 10.1007/s40200-022-01015-1
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of diurnal and nocturnal glucose exposures to HbA1c in type 1 diabetes males: a pooled analysis

Abstract: Purpose The exact contribution of daily glucose exposure to HbA1c in people with type 1 diabetes (T1D) remains controversial. We examined the contribution of pre- and postprandial glycaemia, nocturnal and early-morning glycaemia, and glycaemic variability to HbA1c levels in T1D. In this analysis, we used clinical data, namely age, BMI and HbA1c, as well as glycaemic metrics (24-h glycaemia, postprandial, nocturnal, early-morning glycaemia, wake-up glucose, and glycaemic variability) obtained over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Previously, it has been demonstrated that variances existed between CGM metrics and HbA1c and could be determined by many factors such as time period, variation in glycation rates, and factors such as anemia. In this study, the factors derived from CGM data contributed >70% of the variance in HbA1c, which is in line with the recently published data conducted among T1D males from Europe 13 . Of note, the non‐glycemia factors included in our study, such as age, BMI, diabetic duration, and Hb level, have a small contribution in HbA1c and there was still approximately 20%–30% of the variance in HbA1c undefined even though the contribution of glycemia was higher among those with HbA1c >7.3% .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previously, it has been demonstrated that variances existed between CGM metrics and HbA1c and could be determined by many factors such as time period, variation in glycation rates, and factors such as anemia. In this study, the factors derived from CGM data contributed >70% of the variance in HbA1c, which is in line with the recently published data conducted among T1D males from Europe 13 . Of note, the non‐glycemia factors included in our study, such as age, BMI, diabetic duration, and Hb level, have a small contribution in HbA1c and there was still approximately 20%–30% of the variance in HbA1c undefined even though the contribution of glycemia was higher among those with HbA1c >7.3% .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the factors derived from CGM data contributed >70% of the variance in HbA1c, which is in line with the recently published data conducted among T1D males from Europe. 13 Of note, the non‐glycemia factors included in our study, such as age, BMI, diabetic duration, and Hb level, have a small contribution in HbA1c and there was still approximately 20%–30% of the variance in HbA1c undefined even though the contribution of glycemia was higher among those with HbA1c >7.3% . Recently, Ajjan and his colleagues had reported a model that incorporated erythrocyte lifespan, attempting to address limitations in laboratory HbA1c.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Postprandial hyperglycemia is independently associated with the development of cardiovascular disease (CVD) in people with T1D [5,6]. Additionally, a recent study found that postprandial glucose exposure is a stronger determinant of HbA1c, than preprandial glucose, nocturnal glucose, and glycemic variability in people with T1D, with the evening meal postprandial period being the single largest contributing factor to HbA1c [7].…”
Section: Introductionmentioning
confidence: 99%